Digital Fiscal Stimulus and SMEs: Insights from Thailand's Half and Half Program - Athiphat Muthitacharoen (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study investigates the impact of Thailand's 'Half and Half' program on SMEs. Designed to boost spending on small food vendors, the program distributes subsidies via a digital platform, granting consumers a fixed-percentage copay on every eligible purchase. I employ a difference-in-difference approach using weekly province-level data from LINE MAN Wongnai. I find that the program significantly elevates sales among participating vendors relative to non-participants. Regarding the underlying mechanism, the findings indicate that the increase in sales is primarily driven by an expansion in the unique customer base, rather than an increase in individual order sizes. Crucially, these positive effects persist even after the program's conclusion, with smaller vendors experiencing more pronounced sustained benefits. This investigation enriches the emerging literature on digital fiscal stimulus, underlining their potential for both immediate and sustained economic impact. The findings bear crucial implications for policymakers navigating fiscal strategies in an increasingly digital economic landscape.
Keywords: D22; H32; O31; 330; fiscal stimulus; digital platform; SME